PERCEPTION OF THE USEFULNESS OF CONTAINER DEVICES BASED ON SIEVE VARIATIONS ON THE QUALITY OF PINE SAP HARVESTING - Abdul Hanan, Ishaq; Jumini, Sri; Khotimah, Khusnul; Arsyad, Muaddiul; Indratama, Andin (BRIN Publishing, 2025)
Open pine resin containers in the form of coconut shells and plastic bowls cause the quality of pine sap to decrease, and it is difficult to obtain premium quality, because of the ingress of dirt. The impurities are in the form of leftover twigs, dry pine leaves, grass, soil, and gravel. In addition, when the wind easily releases the coconut shell because the binding is not strong enough with the pine tree. The shell’s pores are finally easily eroded by rain due to the sawing process. Open containers (without covers) are very susceptible to producing less pure pine sap because they are mixed with impurities that fall into the container. They will be difficult to decompose if the dirt is small because the impurities can easily pass through the filter. This study aims to determine the perception of the usefulness of a container tool based on filter variations on the quality of pine resin harvesting. The study was conducted with a quantitative descriptive approach. Data collection was carried out using a questionnaire technique that was given to users, namely pine farmers. Data analysis was carried out using descriptive statistics, namely calculating the average of the results of the questionnaire recapitulation. The study results showed that the community agreed that the farmers can use the innovation of a pine sap container based on a sieve in harvesting pine sap. The tool has good durability, is easy to maintain, is easy to use, practical, effective use, ; is safe, is easy to store, does not produce waste, and has excellent benefits and functions. The impact of using this tool is that Perhutani no longer needs to look for tools, and the quality of the pine sap harvested with this sieve-based pine sap container is no longer in doubt. With good quality harvested pine sap, the income of the pine sap farmer community has increased